2018
DOI: 10.1038/cr.2018.2
|View full text |Cite
|
Sign up to set email alerts
|

Eosinophil-derived CCL-6 impairs hematopoietic stem cell homeostasis

Abstract: Eosinophils (Eos) have been long considered as end-stage effector cells in the hierarchical hematopoietic system. Numerous lines of evidence have suggested that Eos are multifunctional leukocytes with respect to the initiation, propagation and regulation of various inflammatory or immune reactions, especially in allergic diseases. Recent studies have shown that Eos are also required for maintenance of bone marrow plasma cells and differentiation of B cells. However, it remains unclear whether Eos contributes t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
31
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 28 publications
(33 citation statements)
references
References 30 publications
1
31
1
Order By: Relevance
“…In a previous study, overexpression of CCL6 accelerated tumor growth and enhanced local and metastasis spread (15). Similarly, our previous work found that eosinophils secrete CCL6 to promote hematopoietic stem cell proliferation and migration during eosinophilic inflammation (14). Here, we found a dominating role of CCL6 in the cross-talk between eosinophils and tumor cells, strengthening the idea that eosinophil-derived CCL6 directly supports the recruitment of tumor cells, thus promoting tumor metastasis.…”
Section: Discussionsupporting
confidence: 87%
“…In a previous study, overexpression of CCL6 accelerated tumor growth and enhanced local and metastasis spread (15). Similarly, our previous work found that eosinophils secrete CCL6 to promote hematopoietic stem cell proliferation and migration during eosinophilic inflammation (14). Here, we found a dominating role of CCL6 in the cross-talk between eosinophils and tumor cells, strengthening the idea that eosinophil-derived CCL6 directly supports the recruitment of tumor cells, thus promoting tumor metastasis.…”
Section: Discussionsupporting
confidence: 87%
“…The balance among the adult SC state of quiescence, proliferation, differentiation, and self-renewal can also be regulated through their interactions with nearby cells in the microenvironment, such as eosinophils, mesenchymal stromal cells (MSCs), ECs, macrophages, leukocytes, and immune cells[ 63 - 66 ]. In addition, cell-cell adhesion molecules such as vascular cell adhesion molecule (VCAM)-1, cadherin, and intercellular CAM-1 (ICAM-1) also play important roles in promoting activation of or maintaining quiescence in adult SCs[ 67 - 69 ].…”
Section: Extrinsic Factors Regulating Adult Sc Quiescencementioning
confidence: 99%
“…Eosinophils are multifunctional leukocytes responsible for initiation, enhancement, and control of the inflammatory and immune responses, especially in allergic diseases[ 70 ]. Eosinophils were shown to disrupt hematopoietic SC homeostasis and quiescence via ROS accumulation, which is induced by secretion of chemokine (C-C motif) ligand 6[ 66 ].…”
Section: Extrinsic Factors Regulating Adult Sc Quiescencementioning
confidence: 99%
“… 17 Recently, we found that eosinophils disrupt HSC homeostasis by impairing HSC maintenance and mobilization primarily through eosinophil-derived mCCL6. 18 The regulatory effects of eosinophils on stem cells suggest that eosinophils may be involved in the initiation of asthmatic pathology. However, the complex roles of eosinophils and effective factors in allergic asthma are still not completely clear.…”
Section: Introductionmentioning
confidence: 99%
“… 24 , 25 Our previous findings have shown the potential contribution of eosinophil-derived mCCL6 to HSC impairment in inflammatory airway disease. 18 However, the precise function of mCCL6 is not well understood, and its pathogenic role in allergic asthma remains unknown; similarly, the roles of hCCL23 and hCCL15 in asthma patients remain to be explored.…”
Section: Introductionmentioning
confidence: 99%